REFLEXÕES SOBRE DIREITOS HUMANOS E O MULTICULTURALISMO NO BRASIL - Michel Canuto de Sena; Heitor Romero Marques; Ady Faria da Silva; Paulo Roberto Haidamus de Oliveira Bastos (TRF2, 2018)
The present study brings an updated approach on the human rights and multiculturalism in Brazil. In this context, we investigated the first countries that have adopted the human dignity as a fundamental right, since only after the World War II the United Nations, took the dignity of the humans as a fundamental principle, inherent in all human beings. Moreover, the study reviews how the human rights are applied in Brazil and how the multiculturalism acts as part of a globalized society which is permeated by violations, always trying to merging cultural manifestations and social movements into the human rights. The objective of this study is to show the importance of human rights and the development of an efficient combination of multiculturalism and human rights in Brazil. As a general rule, this study was based on bibliographic documents on human rights; and multiculturalism.